Mengimplementasikan Komunikasi Islam Pada Pemerintahan Aceh Dengan Dewan Perwakilan Rakyat Aceh (DPRA) Dalam Mewujudkan Pembangunan - Sulaiman, Azman; Abdullah, Abdullah; Aminullah, Muhammad (Al-Fikrah, 2024)
Aceh is a region that has been granted special autonomy since 2001 as an effort to increase and accelerate development and prosperity in Aceh. This article tries to offer the concept of building Islamic communication to create harmonious relations between the Aceh government and the Aceh People's Representative Council (DPRA). This study was qualitative and carried out by applying content analysis methods. This analysis is related to the values, principles of Islamic communication contained in the book of the Quran, and also takes documentation data from the internet and news links related to the implementation of Islamic communication in realizing development in Ace. The results obtained show that Islamic communication is very important to be implemented in the institution by applying Islamic values and principles. Islamic communication has many contexts, including in building people's harmony and in da'wah activities as a development communicator. In addition, it is important to hold a key role in the effectiveness of government policy implementation by using good communication and compiling a comprehensive communication plan.